Comparative Analysis of Incisor Positioning and Alveolar Bone Thickness using Lateral Cephalograms - Ahmad, Sadia Nisar; Ahmad, Ashfaq; Ullah, Saqib; Kayani, Harmain; Khattak, Rabia; Ullah, Saif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the comparative analysis of incisor positioning and alveolar bone thickness using lateral cephalograms. Study Design: Cross-sectional analytical study Place and Duration of Study: Department of Orthodontics, Bacha Khan College of Dentistry, Mardan from 4th August 2021 to 31st December 2021. Methodology: Fifty class II malocclusion participants were enrolled having deviation from 1mm of root positioning. Lateral-cephalometric images were taken and compared with standard 50 normal optimal occlusions. L1-lab to L1 ling distance was added for calculating the total mandibular alveolar process thickness and wits calculated. The inclination between maxilla and mandibular central incisor and was measured through formation of acute angle between teeth long axes and perpendicular line with occlusal plane. Results: In cases of class II malocclusions majority of the patient were within the age of 15-30 years with a mean age as 38.3±3.9 years. Wits was -0.72±2.5 in normal optimal occlusion verses 2.47±1.88 in class II malocclusion. Conclusion: A significant variance was observed between alveolar (AV) processes of class II malocclusion patients with their comparative lateral cephalogram imaging of normal optimal occlusion.